The Administration of Dutch Teak Leaf Tea Extract (Guazama Ulmifolia lamk) in Reducing Cholesterol Levels in Depo Acceptors - Khobibah, Khobibah; Nurhidayati, Tri; Ruspita, Mimi; Rozikhan; Martanti, Listyaning Eko (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Depo hormonal contraceptives are significantly effective contraceptives with a low failure rate. Women who apply this contraceptive may experience several side effects on fat metabolism, which is an increase and decrease in total cholesterol (TC), triglycerides (TG), and low-density lipoprotein cholesterol (LDL-C). The objective of this study was to identify the influence of Dutch teak leaves (Guazuma Ulmifolia Lamk) on the cholesterol levels in the Depo acceptors. Quasi-experiment research design with one group pretest posttest design model. The pretest was completed first by the total number of samples which is 60 respondents. Furthermore, 250 ml of Dutch teak tea is consumed every morning and evening after eating. The intervention lasted two weeks, followed by a retest (posttest). Dutch tea pre and post results were analyzed employing t-test statistics on variable body weight (p = 0.706), systolic blood pressure (p = 0.322), and cholesterol (p = 0.001), and the Wilcoxon test on diastolic pressure variables (p = 0.043) and triglycerides (p = 0.417). With a p-value of 0.001, it demonstrates that there is a significant difference in cholesterol levels after being treated with Dutch teak tea. With a p-value greater than 0.05, there was no difference in triglycerides, weight, or blood pressure after receiving Dutch teak tea treatment. An increase in cholesterol levels is one of the side effects of DMPA acceptors. Therefore, consuming Dutch teak leaves is an alternative treatment option.